Is Czech health care going to be lean? - Vitásková, Edita (Univerzita Pardubice, 2015)
There is a growing interest in applying lean in healthcare. Healthcare services around the world have adopted industrial engineering methods and process improvement methodologies from the manufacturing sector, known as lean production. The aim of this paper is to provide a review of the existing literature on lean healthcare and to publish basic results of survey focused on Czech medical staff's knowledge of lean healthcare philosophy. Focus of this article is not to detail lean principles and concepts. The article explores challenges and opportunities faced by organizations that intend incorporating lean management principles and presents the specific context of the healthcare industry. Though there seems to exist an agreement about the potential of lean healthcare, it remains a challenge for academics and practisioners to evaluate lean healthcare under a more critical perspective. This paper aims to describe how the lean healthcare philosophy has being applied and to asses how trends and methods of approach in lean healthcare have evolved over the years.
Keywords: lean management; healthcare; quality; continuous improvement; customer value; I19